Oxygen-rich Long Period Variables in the X-Shooter Spectral Library. Issue Volume 14:Issue S343(2019) (August 2018) - Lançon, Ariane; Gonneau, Anas; Trager, Scott C.; Prugniel, Philippe; Arentsen, Anke; Chen, Yanping; Dries, Matthijs; Loup, Cécile; Lyubenova, Mariya; Peletier, Reynier; Telliez, Laure; Vazdekis, Alexandre; et al.
Abstract: The X-Shooter Spectral Library (XSL) contains more than 800 spectra of stars across the color-magnitude diagram, that extend from near-UV to near-IR wavelengths (320-2450 nm). We summarize properties of the spectra of O-rich Long Period Variables in the XSL, such as phase-related features, and we confront the data with synthetic spectra based on static and dynamical stellar atmosphere models. We discuss successes and remaining discrepancies, keeping in mind the applications to population synthesis modeling that XSL is designed for.